2009
DOI: 10.1016/j.neulet.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Central neuronal mechanisms of intestinal electrical stimulation: Effects on duodenum distention-responsive (DD-R) neurons in the VMH of rats

Abstract: Intestinal electrical stimulation (IES) has been shown to produce inhibitory effects on gastric contractions, gastric emptying, food intake and body weight in rats and dogs, suggesting a therapeutic potential for obesity. The aims of this study were 1) to test the hypothesis that the neurons in the VMH are involved in the central mechanisms of IES treatment for obesity; 2) to compare the effects of IES at the duodenum and IES at the ileum on neuronal activities of the VMH; 3) to better understand if the neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The increase in satiety would lead to a reduction in food intake and subsequent weight loss. This central neuronal mechanism was demonstrated with GES [42] and DES [43] and also implicated in our preliminary study (unpublished data).…”
Section: Discussionsupporting
confidence: 80%
“…The increase in satiety would lead to a reduction in food intake and subsequent weight loss. This central neuronal mechanism was demonstrated with GES [42] and DES [43] and also implicated in our preliminary study (unpublished data).…”
Section: Discussionsupporting
confidence: 80%
“…In one previous study, IES was reported to activate the neurons in the nucleus tractus solitarii, suggesting a vagal afferent pathway (23). In a more recent study, IES was found to activate the neurons in the ventromedial nucleus, which is related to satiety (29).…”
Section: Discussionmentioning
confidence: 91%
“…Compared to sham IES which only slightly increased GLP-1 secretion at 15 min after oral glucose, IES of both 0.3 and 3 ms significantly enhanced the secretion of GLP-1. IES was reported to modulate neuronal activities in the nucleus of the solitary tract and hypothalamus in rats via the activation of vagal afferent pathway [29,30]. This rapid rise in GLP-1 secretion which was augmented by IES may be mediated indirectly through a neuro/endocrine pathway, rather than through forwarding the nutrient for the direct interactions of the luminal contents with L cells [31].…”
Section: Discussionmentioning
confidence: 99%